The Factors Affecting Digital Bank Services Adoption Using Trust as Mediating Variable - Kantika Kantika; Florentina Kurniasari; Mulyono Mulyono (Journal of Business and Management Review, 2022)
The rise of the internet in Indonesia have pushed businesses to speed up the digital transformation of the financial sector, including banking and financial technology. This has led to changes in the structure of the economy and how businesses compete and collaborate. A Digital Bank is one of the business model innovations because it relies on a digital ecosystem. It is important for people to have trust in digital bank services because this digital bank doesn't have a branch office to provide its services, and there aren't adequate regulations to protect data or security system. This study aims to determine what factors influence customers' adoption of a digital bank by analyzing the effects of perceived security, perceived enjoyment, financial literacy, and brand image on the adoption of digital payment services using trust as a mediating variable. This research was conducted using quantitative methods with Digital Bank users as the respondents. The results of the study indicate that perceived security, perceived enjoyment, financial literacy, and brand image have a positive and significant influence on the adoption of digital bank services in Indonesia, where trust variable has the greatest effects on the adoption of Digital Bank services. Therefore, Digital Bank companies need to increase user trust by increasing IT resources, developing attractive and useful digital platforms, and building a good image of the Digital Bank industry as a trusted service.